Marketing Performance Measurement Management: Study of Selected Small and Medium Scale Businesses in Nigeria - Oko, Augustine Egwu; Kalu, Innocent N (Advances in Social Sciences Research Journal, 2014)
Small and medium scale businesses constitute over 70% of the industrial sector of Nigeria. Unfortunately however these firms, based on estimation of performance do not contribute significantly for the macro development of the society. This poor level of contribution is attributed to paucity in the adoption of marketing performance measurement management principles and techniques. This work for the assessment of the rate and level of adoption use of marketing and accounting metrics studied firms in selected industrial sector of the economy. This is based on sample population determined using the yard mathematical notation and set of questionnaire assessed using Likert rank order scale and pearson correlation co-efficient R. Findings include that small and medium scale businesses find it difficult to create and sustain linkage between marketing as a unit of business system with the entire system; paucity in tracking metrics that relate to programmes; gross inability at managing changes among others. Recommended are efficiency in corporate goals and marketing objectives determination given the peculiar business environment; adoption of acceptable marketing metrics for performance evaluation; adoption of acceptable marketing metrics for performance evaluation; adoption of regular performance audit programmes and adoption of modern methods of data capturing and analysis based on the use of skilled personnel.